Comparison of different correlational techniques in estimating the total generated power of neighboring photovoltaic systems - Al-Hilfi, H.; Shahnia, Farhad; Abu-Siada, Ahmed (2016)
© 2016 IEEE.Several techniques are proposed in the literature on defining the spatial and temporal correlation of a group of distributed photovoltaic systems in close proximity in order to estimate the total generated power under various weather conditions. This paper evaluates the performance of different correlational techniques while considering the impact of the speed of a passing cloud. The study considers ten distributed photovoltaic systems installed at the University of Queensland and evaluates the outcomes based on each investigated technique over two sample days. Wavelet transform analysis is utilized when defining the estimated total power. Through MATLAB-based numerical analysis, the error between the outcomes of these techniques at various cloud speeds is calculated and compared.